Mosquito (Diptera: Culicidae) diversity of a forest-fragment mosaic in the Amazon rain forest - Hutchings, Rosa Sá Gomes; Sallum, Maria Anice Mubeb; Hutchings, Roger William (Journal of Medical Entomology, 2011)
To study the impact of Amazonian forest fragmentation on the mosquito fauna, an inventory of Culicidae was conducted in the upland forest research areas of the Biological Dynamics of Forest Fragments Project located 60 km north of Manaus, Amazonas, Brazil. The culicid community was sampled monthly between February 2002 and May 2003. CDC light traps, flight interception traps, manual aspiration, and net sweeping were used to capture adult specimens along the edges and within forest fragments of different sizes (1, 10, and 100 ha), in second-growth areas surrounding the fragments and around camps. We collected 5,204 specimens, distributed in 18 genera and 160 species level taxa. A list of mosquito taxa is presented with 145 species found in the survey, including seven new records for Brazil, 16 new records for the state of Amazonas, along with the 15 morphotypes that probably represent undescribed species. No exotic species [Aedes aegypti (L.) and Aedes albopictus (Skuse)] were found within the sampled areas. Several species collected are potential vectors of Plasmodium causing human malaria and of various arboviruses. The epidemiological and ecological implications of mosquito species found are discussed, and the results are compared with other mosquito inventories from the Amazon region. © 2011 Entomological Society of America.
Keywords: Animals; Classification; Demography; Ecosystem; Genetics; Mosquito; Tree; Animal; Culicidae; Demography; Ecosystem; Trees; Aedes Aegypti; Aedes Albopictus; Arbovirus; Culicidae; Diptera